Changing ability to pay for housing into effective demand: Evidence of institutional constraints from the slums in India. (February 2017) - Ram, Padmini; Needham, Barrie
Abstract: Informal land and housing markets operating in the slums of Raipur give further evidence about what was already known: that, slums do not consist of homogeneous households and that some households are capable and willing to pay for their dwelling in the formal market if the institutional constraints are addressed. Then, what are the demand constraints they face? The existing literature about creating an affordable housing market focusses on the constraints in getting credit and mortgages. In our opinion, this is too narrow, for it ignores the institutional setting and the political context in which the slum dwellers are operating. This paper presents the perspective of the slum dwellers, and the barriers they face in accessing formal affordable housing. The constraints have been classified as those relating to housing as a commodity and those related to the process of acquiring the commodity. It uses descriptive statistics from a survey of 211 households conducted in the slums of Raipur, India, along with anecdotal and personal accounts of the slum dwellers gathered through the informal discussions. Highlights: This article investigates the demand constraints to formal affordable housing. Presents evidence from informal housing markets in the slums of Raipur, India. Uses descriptive statistics from a survey of 211 households. Also presents some anecdotal and personal accounts of the slum dwellers.